Analisis Pengembangan Jaringan Bisnis pada Usaha YOI Milk Terhadap Keputusan Pengembangan Produk - Resya Dwi Marselina; Hamdani Hamdani; Agus Riyanto; Putri Utami; Riski Rilda Supriyanti; Sipa Anggraeni Pratama Nur (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research is motivated by widespread business networks in the business world and raises fierce business competition. To respond to this, the author conducted a business network research conducted by MSMEs Yoi Milk. The objectives that must be achieved in this study include: (1) to find out what the founders of Yoi Milk did to build their business network. (2) to find out how marketing is done by Yoi Milk. (3) to find out how the financial management is carried out by Yoi Milk in order to get profits in accordance with what the business wants. This research was conducted directly by the founder of Yoi Milk. This research seeks business networks carried out by Yoi Milk business entrepreneurs to decide on product development starting from marketing carried out to products marketed to consumers. This research uses qualitative methods, one of which is interviewing Yoi Milk business actors about marketing, sales, and financial management carried out for profit.